Intestinal and Systemic Immune Responses upon Multi-drug Resistant Pseudomonas aeruginosa Colonization of Mice Harboring a Human Gut Microbiota - von Klitzing, Eliane; Ekmekciu, Ira; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2017)
The World Health Organization has rated multi-drug resistant (MDR) Pseudomonas aeruginosa as serious threat for human health. It is, however, unclear, whether intestinal MDR P. aeruginosa carriage is associated with inflammatory responses in intestinal or even systemic compartments. In the present study, we generated with respect to their microbiota “humanized” mice by human fecal microbiota transplantation of secondary abiotic mice. Following peroral challenge with a clinical P. aeruginosa isolate on two consecutive days, mice harboring a human or murine microbiota were only partially protected from stable intestinal P. aeruginosa colonization given that up to 78% of mice were P. aeruginosa-positive at day 28 post-infection (p.i.). Irrespective of the host-specificity of the microbiota, P. aeruginosa colonized mice were clinically uncompromised. However, P. aeruginosa colonization resulted in increased intestinal epithelial apoptosis that was accompanied by pronounced proliferative/regenerative cell responses. Furthermore, at day 7 p.i. increased innate immune cell populations such as macrophages and monocytes could be observed in the colon of mice harboring either a human or murine microbiota, whereas this held true at day 28 p.i. for adaptive immune cells such as B lymphocytes in both the small and large intestines of mice with murine microbiota. At day 7 p.i., pro-inflammatory cytokine secretion was enhanced in the colon and mesenteric lymph nodes, whereas the anti-inflammatory cytokine IL-10 was down-regulated in the former at day 28 p.i. Strikingly, cytokine responses upon intestinal P. aeruginosa colonization were not restricted to the intestinal tract, but could also be observed systemically, given that TNF and IFN-γ concentrations were elevated in spleens as early as 7 days p.i., whereas splenic IL-10 levels were dampened at day 28 p.i. of mice with human microbiota. In conclusion, mere intestinal carriage of MDR P. aeruginosa by clinically unaffected mice results in pro-inflammatory sequelae not only in intestinal, but also systemic compartments.